ANALISIS KESIAPAN IMPLEMENTASI REKAM MEDIS ELEKTRONIK DENGAN PENDEKATAN SUMBERDAYA MANUSIA, BUDAYA ORGANISASI, TATA KELOLA KEPEMIMPINAN DAN INFRASTRUKTUR DI RS CITAMA - Rumondang, Christin; Aziz, Abdul; Novita, Astrid (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
A hospital is a health facility and a place for carrying out health efforts, as well as an organization with an open system and always interacting with its environment to achieve a dynamic balance and has the main function of providing health services to the community. The higher a community's intelligence and social economy, the better their knowledge of disease, costs, administration and healing efforts. Data management in hospitals is one of the important components in realizing an information system in hospitals. Manual data management has many weaknesses, apart from taking a long time, its accuracy is also less acceptable, because the possibility of errors is very large. This research method uses a comparative descriptive method with a qualitative approach. There were 7 informants involved in this research consisting of: Hospital Director, Head of Finance, Head of Medical Services, Head of IT, Medical Records Officer, Doctor, Nurse. The results of the research showed that Citama Hospital currently has three IT personnel with educational specifications of S1 Computer and D3 Computer, this number has been adjusted to the needs of IT personnel at the hospital. The medical records staff consists of six people with a D3 degree in Medical Records and three with high school education. Judging from the results of governance and leadership readiness, Citama Hospital is in a fairly ready condition, namely that the leadership already has a discourse on implementing RME for Inpatients which will be scheduled to start at the end of 2022 or early 2023 where Citama Hospital has already prepared an information system that has been prepared. computerized but in implementing electronic medical records, hospital leaders have not yet formed a special team to speed up electronic medical records and there is also no strategy to speed up the implementation of electronic medical records. The successful implementation of RME at Citama Hospital requires a joint commitment from management and all human resources regarding changes from the comfort zone to manual medical records so far. The results of the research can be continued training to improve the skills of electronic medical record users, so that it will increase the benefits and advantages of electronic medical record users because currently the development of science and information technology is very rapid.